2024
DOI: 10.1002/adma.202313156
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Grain Boundaries Promoted Hydrogen Production for Industrial‐Grade Current Density

Yu Cheng,
Huanyu Chen,
Lifang Zhang
et al.

Abstract: The development of efficient and durable high‐current‐density hydrogen production electrocatalysts is crucial for the large‐scale production of green hydrogen and the early realization of hydrogen economic blueprint. Herein, we have successfully driven the evolution of grain boundaries through Cu‐mediated NiMo bimetallic oxides (MCu‐BNiMo), which leading to the high efficiency of electrocatalyst for hydrogen evolution process (HER) in industrial‐grade current density. The optimal MCu0.10‐BNiMo demonstrated ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…It meant the detachment of hydrogen and the release of active sites . The calculation indicated that electrons from the Au substrate transfer to Pd with the increasing strain, thereby weakening the ability of Pd to adsorb hydrogen atoms . This makes hydrogen atoms desorb from the surface more easily and release the active sites.…”
mentioning
confidence: 99%
“…It meant the detachment of hydrogen and the release of active sites . The calculation indicated that electrons from the Au substrate transfer to Pd with the increasing strain, thereby weakening the ability of Pd to adsorb hydrogen atoms . This makes hydrogen atoms desorb from the surface more easily and release the active sites.…”
mentioning
confidence: 99%